Prevalency of smoking in medicine students - Magliari, Rafael Thiesen; Pagliusi, Alexandre Lima; Previero, Bruno Manetti; Menezes, Fernando Reis; Feldman, Andre; Novo, Neil Ferreira (Revista de Medicina, 2008)
This is a epidemiological paper concerning the use of cigarettes by medicine students and also a literature review based on several different articles. According to the World Health Organization (WHO), smoking is the main cause of preventable diseases in the planet and is directly responsible for about 8 millions deaths a year. Such numbers aren’t a big surpise for any educated reader, but what is interesting is that despite this, the number of smokers are progressively growing. The medical class, which are the people responsible for informing and warning the population have agreat percentage of smokers. The present paper illustrate this fact, through a questionnaire answered by 241 students with a percentage of 17.8% smokers. This fact may be related to the stress involved in the medical course, associated with lack of time in their private lives. The author concludes that having reliable smoking data about the medicine students is of vital importance, demonstrating the need of emphases in prevention campaigns in all society classes, especially among health students, who will be the main agents in promoting health in the future.